Indian Research Information Network System (IRINS): A Review - Sab M, Chaman (Journal of Data Science, Informetrics, and Citation Studies)
A web-based Research Information Management (RIM) service called IRINS was created by the Information and Library Network (INFLIBNET) Centre. For Indian academic and research organisations, this cutting-edge platform is created to simplify the management of scholarly communication operations. IRINS gives customers the tools they need to efficiently gather, curate, and present the results of their research thanks to its user-friendly interface and integration possibilities. Additionally, it promotes academic networking possibilities, fostering cooperation and knowledge exchange among academics and researchers. IRINS democratises research administration by providing free software as a service, which is especially advantageous for smaller universities with constrained funding. Additionally, it makes the intake of academic papers from diverse sources simpler thanks to its interface with academic identification services, improving the correctness and simplicity of data administration. IRINS is a promising organisation in a research environment that is rapidly changing.
Keywords: IRINS; Indian Research Information Network System (IRINS); VIDWAN; INFLIBNET; NMICT; Profiles of Scientists.